Evaluation of the hardness distribution and fracture location in friction stir welded AA6063 pipe butt joints - Ismail, A. (Springer Verlag, 2018)
Frictional heat generated during the friction stir welding (FSW) process will somehow affect the mechanical properties of friction stir welded joints. In this present study, the FSW of aluminium alloy (AA) 6063 pipe butt joints with 5 mm wall thickness has been performed, and the evaluation of fracture and hardness distribution across the weld cross section is primarily discussed. Several selected rotational and travel speeds are used for specimen preparation. It was found that the fracture location closely matched with the lowest hardness region either on the advancing or retreating side of the welded joints. Â© Springer International Publishing AG 2018.